2014
DOI: 10.1021/ja510603w
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Construction of Tetrasubstituted Stereogenic Carbons through Brønsted Base Catalyzed Michael Reactions: α′-Hydroxy Enones as Key Enoate Equivalent

Abstract: Catalytic and asymmetric Michael reactions constitute very powerful tools for the construction of new C-C bonds in synthesis, but most of the reports claiming high selectivity are limited to some specific combinations of nucleophile/electrophile compound types, and only few successful methods deal with the generation of all-carbon quaternary stereocenters. A contribution to solve this gap is presented here based on chiral bifunctional Brønsted base (BB) catalysis and the use of α'-oxy enones as enabling Michae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 183 publications
0
61
0
Order By: Relevance
“…[61] In this context, the Steglich rearrangement is an interesting approach, which involves an O-to C-acyl migration, with formation of a new stereogenic center. [61] In this context, the Steglich rearrangement is an interesting approach, which involves an O-to C-acyl migration, with formation of a new stereogenic center.…”
Section: Steglich Rearrangementmentioning
confidence: 99%
“…[61] In this context, the Steglich rearrangement is an interesting approach, which involves an O-to C-acyl migration, with formation of a new stereogenic center. [61] In this context, the Steglich rearrangement is an interesting approach, which involves an O-to C-acyl migration, with formation of a new stereogenic center.…”
Section: Steglich Rearrangementmentioning
confidence: 99%
“…[33] In 2014, Palomo and coworkers reported that glutamic acid derivative 53 can be obtained through the asymmetric conjugate addition of azlactones using chiral squaramide C2 as the catalyst (Scheme 19). [34] In 2015, Palomo and coworkers demonstrated for the first time that various N-substituted a-amino acid derivatives could be obtained in excellent diastereoselectivities and enantioselectivities through the enantioselective 1,4-addition reaction of imidazolones to nitroolefins (Scheme 20). [35] Scheme 8.…”
Section: Enantioselective Synthesis Of Other Heteroatomcontaining Commentioning
confidence: 99%
“…For example in 2013, Palomo and co-workers introduced 5 H -thiazol-4-ones as a new class of sulfur-containing pro-nucleophiles in a highly enantio- and diastereoselective conjugate addition to nitroalkenes, providing α,α-disubstituted α-mercapto carboxylic acids [5]. Since then, several asymmetric variants using 5 H -thiazol-4-ones as nucleophiles have been disclosed; such as amination [6], allylation [7], conjugate addition to enones [8], and γ-addition with allenoates [9]. All these examples focused on nucleophilic addition reactions of the C5 atom of 5 H -thiazol-4-ones.…”
Section: Introductionmentioning
confidence: 99%